Seroprevalence of Chikungunya virus infection in a Tertiary Care Hospital, Warangal, Telangana, South India: Seroprevalence of Chikungunya virus infection - Krishna, Gudikandula; Sreedevi, S; Khan, Abdul (Clinical and Research Journal in Internal Medicine, 2023)
Introduction: The Chikungunya virus, an Alpha virus belongs to the Togaviridae family which infects via the vector Aedes spp. mosquitoes, is the cause of the Chikungunya sickness. The most prevalent symptoms are an abruptly rising temperature, rash, and acute arthralgia. Similar to other arboviral diseases such as Dengue and Japanese B encephalitis infections, it is a serious public health issue. Methods: A total of 3027 blood samples were received from suspected cases of Chikungunya in the Tertiary Care Hospital, Warangal, Telangana. Over a period of 17 months, this study was conducted. Nearly 5-10ml of blood was collected from the patients after 5 days of fever, and the serum was separated. Using an IgM antibody capture ELISA kit manufactured by NIV (NIV, Pune, India). Results: In our study population of 3027 during 12 months, 313 Chikungunya cases (10.34%) were found to be seropositive for Chikungunya by IgM ELISA. Most cases were from 0-10 Years (24.60%), followed by 11-20 years (17.25%). Regarding the sex ratio of the total affected cases, 53.35% were males, and 46.64% were females. A maximum number of positives were seen in September, November, and October, which were found to be 35.46%, 18.84%, and 17.57%. Conclusion: The study found a seroprevalence rate of 23.06% for Chikungunya, with a notable increase in frequency during the monsoon season. Additionally, the virus was found to disproportionately affect individuals in the productive age range of the population.